2010
DOI: 10.1063/1.3518286
|View full text |Cite
|
Sign up to set email alerts
|

Detailed study of the influence of surface misorientation on the density of Anti-Phase Boundaries in 3C-SiC layers grown on (001) silicon

Abstract: In this work we investigated the influence of the Si substrate misorientation and 3C-SiC film thickness on the density of Anti-Phase Boundaries, in order to better understand the mechanism of antiphase domain annihilation. The two highlights in our work are the utilization of [001] orientated Si on-axis wafer with spherical dimples, which gave us access to a continuum of off-cut angles (0° to ~11° ) and directions, and the deposition of elongated silicon islands on the surface of 3C-SiC epilayers, which improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…for which differences in sublattice allocation result in a 90° in plane rotation of crystalline directions between one grain and its neighbour, the two diffraction sets on azimuth scans demonstrates the possibility to have four distinct Si grain orientation taking into account 3C-SiC APDs. Moreover, it is well known that APDs density can be reduced or supressed by using off axis Si substrate and/or by growing thick 3C-SiC epilayers [13]. In the present work, the 4°off axis 3C-SiC epilayer over which we have deposited Si film is about 1.5µm thick.…”
Section: Resultsmentioning
confidence: 80%
“…for which differences in sublattice allocation result in a 90° in plane rotation of crystalline directions between one grain and its neighbour, the two diffraction sets on azimuth scans demonstrates the possibility to have four distinct Si grain orientation taking into account 3C-SiC APDs. Moreover, it is well known that APDs density can be reduced or supressed by using off axis Si substrate and/or by growing thick 3C-SiC epilayers [13]. In the present work, the 4°off axis 3C-SiC epilayer over which we have deposited Si film is about 1.5µm thick.…”
Section: Resultsmentioning
confidence: 80%
“…In this way, not all the SFs along the plane (−1−11) are suppressed. At the same time, we observed that this cutting direction does not lead to a complete suppression of the APBs (SEM images not reported here), which act as a source and annihilation point for the SFs [ 27 ]. This leads to an increase in the density of the SFs that reach the surface.…”
Section: Resultsmentioning
confidence: 88%
“…Recently, we have studied the influence of surface misorientation on the density of Anti-Phase Boundaries (APB) in 3C-SiC layers grown on silicon, using the method proposed by Ishida [24]. Based on these results, we have investigated, in more details, the growth mechanisms of the silicon islands in order to try to obtain a continuous and monocrystalline silicon layer.…”
Section: Interest Of Si/3c-sic/si Heterostructure For Afmmentioning
confidence: 99%